2020
DOI: 10.1002/mame.202000137
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Flame Retardancy, Smoke Suppression, and Mechanical Enhancement of β‐FeOOH@Metallo‐Supramolecular Polymer Core–Shell Nanorod Modified Epoxy Resin

Abstract: A metallo-supramolecular polymer poly{4-(((3,4-dihydroxyphenyl) (6-oxidodibenzo[c,e][1,2]oxaphosphinin-6-yl)methyl)amino)phenyl-2,2-dimethylbutanoate} (HP) is synthesized through a Kabachnik-Fields reaction. Then HP is coated on the surface of β-FeOOH by coordination interaction to generate organic-inorganic hybrid β-FeOOH@HP (Fe@P) nanorods, which are used for preparing flame retardant epoxy resin (EP) nanocomposites. The structure of HP is characterized by nuclear magnetic resonance and fourier transform inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Non‐halogenated polymer systems are typically have LOI values over the threshold of 26, attempting to exhibit self‐extinguishing features. [ 30 ] According to TGA data, all of the synthesized polybenzoxazines in the current work have LOI values that are higher than the threshold value of 26 and they display strong self‐extinguishing characteristics with excellent thermal stability.…”
Section: Resultsmentioning
confidence: 94%
“…Non‐halogenated polymer systems are typically have LOI values over the threshold of 26, attempting to exhibit self‐extinguishing features. [ 30 ] According to TGA data, all of the synthesized polybenzoxazines in the current work have LOI values that are higher than the threshold value of 26 and they display strong self‐extinguishing characteristics with excellent thermal stability.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, the values of the LOI were also ascertained for the flame retardant behaviour of the neat sesamol-based polybenzoxazines and composites. Using the char yield value, the LOI value of the neat polybenzoxazine and composites were calculated using the van Krevelen and Hoftyzer equation: 63–65 LOI = 17.5 + 0.4 ( σ )where σ is the percentage char yield of the remains of polymeric materials at 850 °C. The poly(S-a), poly(S-dde), poly(S-ddm), and poly(S-ffa)benzoxazines, as well as the (3-glycidyloxypropyl)trimethoxysilane (GPTMS) functionalized bio-silica and GCN-c reinforced benzoxazine composites, possessed excellent thermal stability compared to that of other synthesised polybenzoxazines, which showed that LOI values were higher than that of the threshold value of 26, which supports a good flame retardant property.…”
Section: Resultsmentioning
confidence: 99%
“…[39,40] Transition metal elements such as Fe, Cu, and Zn were found to improve smoke suppression and reduce the smoke toxicity of resins. [41][42][43][44] In particular, nanomaterials with Zn as the metal source showed excellent characteristics, such as non-mobility, piezoelectricity, and environmental friendliness. Further, they have been widely used in optoelectronic devices, solar cells, and biosensors.…”
Section: Doi: 101002/mame202200461mentioning
confidence: 99%